Validation of the Neuropathologic Criteria of the Third Consortium for Dementia with Lewy Bodies for Prospectively Diagnosed Cases - Fujishiro, Hiroshige (2008)
There is limited information on the validity of the pathological criteria of the Third Consortium on Dementia with Lewy bodies (CDLB) and none based upon prospectively diagnosed cases. In this study the core clinical features of dementia with Lewy bodies (DLB) and the suggestive clinical feature of rapid eye movement sleep behavior disorder were assessed using a battery of standardized clinical instruments in 76 patients with the clinical diagnosis of either DLB or Alzheimer disease. At autopsy, 29 patients had high-likelihood, 17 had intermediate-likelihood and 6 had low-likelihood DLB pathology. The frequency of core clinical features and the accuracy of the clinical diagnosis of probable DLB were significantly greater in high-likelihood than in low-likelihood cases. This is consistent with the concept that the DLB clinical syndrome is directly related to Lewy body pathology and inversely related to Alzheimer pathology. Thus, the Third CDLB neuropathological criteria scheme performed reasonably well and is useful for estimating the likelihood of the premortem DLB syndrome based upon postmortem findings. In view of differences in the frequency of clinically probable DLB in cases with Braak NFT stages V (90%) and VI (20%) and diffuse cortical Lewy bodies, a possible modification of the scheme considering cases with NFT stage VI to be low-likelihood DLB is suggested.